The Taki Onqoy and Andean society (Huamanga, 16th century) - Stern, Steve (1982)
This article examines the response of the Andean peoples to a serious crisis produced in the first decades of Spanish colonial domination. It is part of the third chapter of a larger study on the struggles of the Andean societies of Huamanga and their impact on the colonial order as a whole, from the beginning of the Spanish conquest until 1640. The second chapter of the study analyzes the multiple forms of alliance and collaboration established between Spaniards and indigenous people during Huamanga's early colonial years, the clash of interests that from the beginning made such an alliance precarious and contradictory, and the growing presence of concerns among the Indians regarding the harmful consequences and unexpected aspects of the Andean-Spanish collaboration.